Cellular evidence for selfish spermatogonial selection in aged human testes - Maher, G; Goriely, A; Wilkie, A (Wiley, 2014)
Owing to a recent trend for delayed paternity, the genomic integrity of spermatozoa of older men has become a focus of increased interest. Older fathers are at higher risk for their children to be born with several monogenic conditions collectively termed paternal age effect (PAE) disorders, which include achondroplasia, Apert syndrome and Costello syndrome. These disorders are caused by specific mutations originating almost exclusively from the male germline, in genes encoding components of the tyrosine kinase receptor/RAS/MAPK signalling pathway. These particular mutations, occurring randomly during mitotic divisions of spermatogonial stem cells (SSCs), are predicted to confer a selective/growth advantage on the mutant SSC. This selective advantage leads to a clonal expansion of the mutant cells over time, which generates mutant spermatozoa at levels significantly above the background mutation rate. This phenomenon, termed selfish spermatogonial selection, is likely to occur in all men. In rare cases, probably because of additional mutational events, selfish spermatogonial selection may lead to spermatocytic seminoma. The studies that initially predicted the clonal nature of selfish spermatogonial selection were based on DNA analysis, rather than the visualization of mutant clones in intact testes. In a recent study that aimed to identify these clones directly, we stained serial sections of fixed testes for expression of melanoma antigen family A4 (MAGEA4), a marker of spermatogonia. A subset of seminiferous tubules with an appearance and distribution compatible with the predicted mutant clones were identified. In these tubules, termed 'immunopositive tubules', there is an increased density of spermatogonia positive for markers related to selfish selection (FGFR3) and SSC self-renewal (phosphorylated AKT). Here we detail the properties of the immunopositive tubules and how they relate to the predicted mutant clones, as well as discussing the utility of identifying the potential cellular source of PAE mutations.